Budaya Populer Dalam Pertunjukkan Reyog Obyogan - Nugroho, Oki Cahyo; Purwanir, Hadi (Universitas Muhammadiyah Ponorogo, 2017)
Pop culture is often associated with a community environment with certain characteristics such as beliefs, rituals, performances, form shows, lifestyle patterns, symbols, language, dress, music, dance, and various models form of human expression, intellectual, and how to communicate in a order a certain time.In Reyog Obyogan performances, pop culture can we find is the traditional musical accompaniment or wasps that incorporate elements of today's popular such as dangdut songs. Not only that, the dancers jathil freely change and adjust according to the demand of the audience or trends that are favored in society. Seeing this paradigm and development, the focus in this research is to look further and in-depth how a popular culture trending affect community shape in a staging performances Reyog Ponorogo in Obyogan form.It also affects the patterns of communication, the message and meaning contained within the show itself. Result of this study showed several behaviors in Reyog Obyogan performances influences to a popular culture that were hits in the present like a concept similar to the dance Edreg Jaipong. Saweran also started a lot in the form of performances Reyog. Song or â€œGendingâ€ in reyog also changing from songs like 'walang kekekâ€ being â€œoplosanâ€' or 'kanggo riko' which is present in vogue in society. The costumes also changed with the entry of sensual especially against Jathil dancers are semi-transparent clothing similar to the Kebaya and colorful. The conclusion of this study prove that folk art as a tradisional performanceÂ be affected things that are popular in the community at large at the time.